ANALISIS ANALISIS DETEKSI FRAUD LAPORAN KEUANGAN DENGAN METODE BENEISH M-SCORE (STUDI KASUS PT BANK TABUNGAN NEGARA PERSERO TBK) - Trusty, Hanna; Fithrayudi Triatmaja, Muhammad (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2023)
The financial statements present important disclosures in maintaining the quality of the capital market also explain the current state of the company and its going concern in the future. However, many financial reports are disclosed as misstatements due to manipulation, falsification, and fraud by changing the value and financial information. Self-detection of financial statement fraud is an important matter that must be prioritized. This study uses the Beneish M-Score model to detect potential manipulation of annual financial reports with case study in PT Bank Tabungan Negara (BTn) Persero Tbk for the 2017-2019 book year. Based on the results of data processing, the M-Score value of the company’s financial statement in 2017, 2018, and 2019 respectively was -2,16; -2,20; and -1,87. Those value were greater than the reference value was -2,22. So it can be concluded that based on this model there was potential for manipulation in PT BTN Persero Tbk’s financial statements. The Beneish M-Score model is used to detect potential financial statement fraud or income manipulation in the company’s financial statements. Moreover this model is very useful for shareholders, investors, and creditors to examine the fairness of company’s financial statement. Keywords : Beneish M-Score, Fraud, Financial Statement, Bank BTN Persero Tbk